Cover Feature: A Structurally Characterized CuIII Complex Supported by a Bis(anilido) Ligand and Its Oxidative Catalytic Activity (Chem. Eur. J. 56/2017). Issue 56 (16th August 2017) - Kochem, Amélie; Molloy, Jennifer K.; Gellon, Gisèle; Leconte, Nicolas; Philouze, Christian; Berthiol, Florian; Jarjayes, Olivier; Thomas, Fabrice
Abstract : Cu II and Cu III complexes were synthesized from an anilinosalen ligand. A metal‐centered single oxidation was ascertained by X‐ray diffraction, which shows a contraction of the coordination sphere by around 0.05 Å. The Cu III complex exhibits an unprecedented NIR band, which arises from an anilido‐to‐copper charge transfer. This complex catalyzes the aerobic oxidation of benzyl alcohol under basic conditions very efficiently. It is in fact more active than galactose oxidase models based on Cu II ‐phenoxyl salen complexes (valence tautomer), showing that the electronic structure is not a key factor in governing the reactivity. More information can be found in the Full Paper by F. Thomas et al. onpage 13929 .